Environmental reporting in the hydropower sector: analysis of EMAS registered hydropower companies in Italy - Comoglio, Claudio; Castelluccio, Stefano; Fiore, Silvia (Frontiers in Environmental Science, 2023)
Hydropower (HP) is a key source of renewable energy, but also poses significant environmental challenges, including habitat fragmentation, hydropeaking and perturbations of flow and sediment regime. The absence of standardized approaches and metrics limits the assessment of HP plants’ environmental performance. This study analyzed how Italian companies managing HP plants, and registered to the European Eco-Management and Audit Scheme (EMAS) in 2022, evaluated their sustainability and publicly disclosed related data. The analysis was based on the environmental statements (ESs) of 206 hydropower plants (29% of Italian HP production in 2019). The applied methodology involved an inventory of the plants and their categorization about technical features and the reporting of technical, environmental, and social aspects. The results of the analysis revealed that the companies rarely described the environmental state of the site, even less frequently adopting quantitative indicators. “Soil contamination”, “biodiversity”, “waste production”, “risk of environmental accidents”, “water pollution and flow management”, and “noise emissions” were the aspects considered most significant. No correlation was found among the significance of an aspect, the number of indicators used to describe the associated impacts, and the number of objectives set for reducing those impacts. “Biodiversity” was mostly described through irrelevant indicators (i.e., total site area) and 76% of the allocated budget was assigned to technical aspects without a clear connection with any environmental improvement. The specific impacts on biodiversity were scarcely reported, mitigation measures were rarely mentioned and with few details. In conclusion, the results of the study highlight the need for specific guidelines, directed to the HP sector, for effectively reporting the environmental performances and the effectiveness of the adopted Environmental Management Systems, while providing valuable information to policymakers and researchers.